Relationship between virus traffic and nitric oxide (NO) production in tobacco roots - Danci, Oana (Acta Biologica Szegediensis, 2009)
Nitric oxide (NO) was proved to have several roles in plant-pathogen interactions from the contribution to the local and systemic induction of defence genes to the infection signalling. The aim of this paper was to prove the involvement of NO as signalling molecule during virus infection and to point out that determination of NO levels can be used as a new method of virus detection in plants. For detection of NO generation in tobacco plants infected by potato viruses X, Y and A, 4,5 diaminofluorescein-diacetate (DAF-2DA) was used. It was found that the infected tobacco roots showed two to three times higher NO accumulation, compared to control. Our results indicated that long distance virus movement through roots occured in the stele using phloem sieve elements, but most of the viruses did not reach meristem and root cap cells. It is suggested that NO is a proper signalling molecule during virus infection and fluorescent detection of NO makes possible to demonstrate the presence of viruses within the plant tissues.